Hubungan Sikap Religius dengan Ketekunan Belajar pada Mata Pelajaran Pendidikan Agama Islam di Kelas V SDIT Syahiral Ilmi - Nurhafifah Nurhafifah; Salmi Wati (ARZUSIN, 2026)
Although religious attitudes and learning perseverance have been the focus of various studies, research that specifically discusses the relationship between religious attitudes and learning perseverance among students in integrated Islamic elementary schools remains limited. This study aimed to analyze the relationship between religious attitudes and students’ learning perseverance in Islamic Religious Education. This study used a quantitative approach with a correlational design, involving 26 fifth-grade students of SDIT Syahiral Ilmi selected through total sampling. Data were collected using questionnaires on religious attitudes and learning perseverance, and were then analyzed using the Pearson Product Moment correlation technique. The results showed a significant relationship between religious attitudes and learning perseverance, with a significance value (Sig. 2-tailed) of 0.002 < 0.05 and a correlation coefficient (r) of 0.589, which falls into the moderately strong category. In addition, most students had religious attitudes in the high category, and all students were in the high category for learning perseverance. These findings contribute to the development of studies on religiosity and learning perseverance in the context of Islamic education, while also broadening understanding of the importance of religious values in shaping students’ learning behavior. The conclusion of this study confirms that religious attitudes play an important role in supporting students’ learning perseverance, so educational institutions need to strengthen religious character development as part of improving the quality of Islamic Religious Education learning.